Communication and Mathematical Disposition Ability throughDiscovery Learning Model in Junior High Schools - Dina, Zinatun Hayati; Ikhsan, Muhammad; Hajidin, Hajidin ((JRAMathEdu) Journal of Research and Advances in Mathematics Education, 2019)
Mathematics is a very abstract lesson and is always connected with numbers and formulas. Many students feel unhappy about mathematics and find difficulties in solving problems in the form of tables, stories, and diagrams. Learning method that can help students in improving mathematical communication and mathematical dispositions can be done through the application of discovery learning models. The purpose of this study was to determine the improvement of students mathematical communication and disposition abilities taught with discovery learning models. This study useda quantitative approach with the type of experimental research and the research design usedtrue pretest and posttest design type experiments. The population in this study were all eighth grade students of SMP N 2 Sigli. The sample was chosen randomly from two classes:classes VIII2 and VIII3. The research instrument used was mathematical communication ability test and mathematical disposition questionnaire. The data analysis of students communication and disposition ability was done by two-way ANAVA test at a significant level of 0.05. The results showed that the improvement of students mathematical communication and disposition skills taught with discovery learning models was better than those taught with conventional approaches. Furthermore, there wasno interaction between discovery learning model and the level of students towards improving communication skills and mathematical dispositions. Therefore, mathematics teachers in SMP N 2 Sigli who teach in class VIII can use discovery learning models in learning to build the next flat side space. Futureresearchers should conduct research at other schools in order to improve students mathematical communication skills in mathematics learning.